A transistorized radiation monitor - Brown, D. C.; Faraday, B. P. (College of Aeronautics, 1956)
This paper describes the investigation of a number of possible semiconductor devices which can be used for the detection of radioactive particles. The sensitivities of two types of transistor (a p-n-p alloy junction and an n-p-n grown junction) and a p-n alloy junction diode operated up to its "avalanche" condition were determined. The possible uses of such detectors are discussed and they are shown to be • particularly suitable where high rates of counting, with good efficiency and small detecting area (or low geometry) are required. A completely transistorized radiation monitor has been developed using a p-n-p transistor as the detector head. This is specifically designed for a-particle detection but the detector head with slight modification should be suitable for proton or neutron detection.